Dentistry Department after COVID - 19 in Indian Medical College - Abhishek (Al Ameen Medical College, 2021)
"Dentistry, also known as dental medicine and oral medicine, is a branch of medicine that consists of the study, diagnosis, prevention, and treatment of diseases, disorders, and conditions of the oral cavity, commonly in the dentition but also the oral mucosa, and of adjacent and related structures and tissues, particularly in the maxillofacial (jaw and facial) area" [1]. Covid-19 is the outbreak of Novel corona virus disease and has been reported in the city of Whuhan, China in the late 2019. The Dentistry is the most affective profession after this Covid-19 in the world [2].